Vertical Array Matched-Field/Mode Processing Results from Marginal Ice Zone Data - Smith, G. B.; Lawrence, Thomas N. (1990)
Availability: Pub. in Jnl. of Acoustical Society of America v87 p2493-2502, 1990. No copies furnished by DTIC/NTIS.